2018
DOI: 10.1155/2018/6473580
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-Gallate Reduces Neuronal Apoptosis in Rats after Middle Cerebral Artery Occlusion Injury via PI3K/AKT/eNOS Signaling Pathway

Abstract: Background/Aims Epigallocatechin-3-gallate (EGCG) has neuroprotective effects and the ability to resist amyloidosis. This study observed the protective effect of EGCG against neuronal injury in rat models of middle cerebral artery occlusion (MCAO) and investigated the mechanism of action of PI3K/AKT/eNOS signaling pathway. Methods Rat models of permanent MCAO were established using the suture method. Rat behavior was measured using neurological deficit score. Pathology and apoptosis were measured using HE stai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 27 publications
2
37
0
1
Order By: Relevance
“…PI3K/Akt is a transmembrane signal transduction cascade involved in the growth and apoptosis of myocardial cells, which also regulate coronary angiogenesis and downstream signal transduction . He et al demonstrated that activating the PI3K/Akt/eNOS signaling pathway attenuates myocardial apoptosis induced by ischemic‐reperfusion (I/R) in mice via cleaving caspase‐3 expression, elevating the Bcl‐2/Bax ratio, and restoring NO production.…”
Section: Introductionmentioning
confidence: 99%
“…PI3K/Akt is a transmembrane signal transduction cascade involved in the growth and apoptosis of myocardial cells, which also regulate coronary angiogenesis and downstream signal transduction . He et al demonstrated that activating the PI3K/Akt/eNOS signaling pathway attenuates myocardial apoptosis induced by ischemic‐reperfusion (I/R) in mice via cleaving caspase‐3 expression, elevating the Bcl‐2/Bax ratio, and restoring NO production.…”
Section: Introductionmentioning
confidence: 99%
“…It follows the mTOR-AMPK pathway in stressed ER and impaired the oxidative stress responses and enhance autophagy-dependent survival. It also promotes cell multiplication, differentiation, neovascularization, tube formation, and cell homing by associating the vascular endothelial growth factor (VEGF), regulation of BAX, Bcl-2, LC3B, caspase-3, mTOR and Beclin-1 [187]. It has also protected HBMVECs from Ischemia/Reperfusion injury by ameliorating apoptosis and autophagy and promoting neurovascularization [105].…”
Section: Vascular Cognitive Impairmentmentioning
confidence: 99%
“…In addition, EGCG (2.5 mg/kg for 2 weeks) in the dentate gyrus has been shown to promote the proliferation of neuronal precursor cells as well as inhibit apoptosis in the hippocampus [ 72 ]. Moreover, EGCG (administered intraperitoneally, at a dose of 20 mg/kg) in rat models with I/R injury reduced neurological deficits, decreased oxidative stress and levels of brain injury markers, promoted neuron survival, and inhibited the apoptosis of neuronal cells through the upregulation of Bcl-2 expression and the downregulation of Bax and Caspase-3 [ 66 ].…”
Section: Flavonoidsmentioning
confidence: 99%